2012
DOI: 10.1097/phm.0b013e318238a0e3
|View full text |Cite
|
Sign up to set email alerts
|

Is Swallowing of All Mixed Consistencies Dangerous for Penetration-Aspiration?

Abstract: Swallowing of MIX is not dangerous, and it is safer for not inducing penetration-aspiration as compared with the swallowing of LIQUID. The risk of penetration-aspiration may be judged depending on not only a food's consistency but also on various factors that affect airway protection, including the texture of food.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
24
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(29 citation statements)
references
References 16 publications
5
24
0
Order By: Relevance
“…Of the 29 studies describing swallowing or oral processing in adults, 27 reported data for healthy adult participants [1945], with two studies restricting their focus to denture wearers [46, 47]. A total of 10 studies reported data for adults with dysphagia [2024, 4852]. Four of these studies described swallowing in stroke patients in comparison to healthy controls [2124] and a 5th paper described a group of patients with dysphagia secondary to Chagas’ disease, again with comparison to a group of healthy controls [20].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Of the 29 studies describing swallowing or oral processing in adults, 27 reported data for healthy adult participants [1945], with two studies restricting their focus to denture wearers [46, 47]. A total of 10 studies reported data for adults with dysphagia [2024, 4852]. Four of these studies described swallowing in stroke patients in comparison to healthy controls [2124] and a 5th paper described a group of patients with dysphagia secondary to Chagas’ disease, again with comparison to a group of healthy controls [20].…”
Section: Resultsmentioning
confidence: 99%
“…Two papers reported data for individuals with dysphagia related to head and neck cancer, in one case following surgical resection of the soft palate [48] and the second exploring post-radiation dysphagia in patients treated for nasopharyngeal carcinoma [49]. The remaining papers described swallowing in patients with Parkinson’s disease [50], in unspecified neurogenic dysphagia [51], or in unspecified dysphagia [52]. Sample sizes ranged from 3 [25] to 205 [24] participants.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…There is also evidence of negative outcomes associated with increased thickness: the IDDSI review [26**] identified greater vallecular residue for thicker consistencies [39,41,50,51] and Troche et al [40] observed a greater number of tongue pumps required to swallow a pudding-thick consistency than a thin liquid. This trend was also recently observed for starch-but not gum-based thickeners [37*] (with equal apparent viscosity) with significantly more oral and pharyngeal residue was apparent for starch vs gum at thicker consistencies.…”
Section: Clinical Evidence Relating To Texture Modification and Swallmentioning
confidence: 99%
“…Thicker liquids were reported to increase the duration of swallowing events in accelerometry [29], electromagnetic articulography [30], ultrasound [31] and surface electromyography signals [32], [33], [34], and also on videofluoroscopy for pharyngeal transit time measures [35], [36], although more recently a study found no effect of thickening on bolus velocity [37]. Regarding dysphagia, several videofluoroscopic studies provided evidence of texture modification having a measurable effect on swallowing efficacy [38], [39], [40], [41], e.g. reduced penetration-aspiration with increasing viscosity [36].…”
Section: Clinical Evidence Relating To Texture Modification and Swallmentioning
confidence: 99%